2016
DOI: 10.1080/21655979.2016.1197029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of protective effects of curcumin, curcumin-β-cyclodextrin nanoparticle and nanoliposomal curcumin on unsymmetrical dimethyl hydrazine poisoning in mice

Abstract: (2016) Comparative analysis of protective effects of curcumin, curcumin-β-cyclodextrin nanoparticle and nanoliposomal curcumin on unsymmetrical dimethyl hydrazine poisoning in mice, Bioengineered, 7:5, 334-341, DOI: 10.1080/21655979.2016 ABSTRACTThe aim of this study was to compare the protective effects of curcumin, curcumin-b-cyclodextrin nanoparticle curcumin (BCD-CUR) and nanoliposomal curcumin (NLC) on unsymmetrical dimethylhydrazine (UDMH) induced poison in mice. Curcumin, BCD-CUR, and NLC were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In the case of CNS and liver damage caused by UDMH, curcumin has a protective effect [ 11 , 12 ]. Researchers in India induced adenomas and colon carcinomas in rats by introducing DMH, and they found that administration of vanadium salt not only increased glutathione S-transferase and cytochrome P450 activity in the liver but also slowed tumor growth [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CNS and liver damage caused by UDMH, curcumin has a protective effect [ 11 , 12 ]. Researchers in India induced adenomas and colon carcinomas in rats by introducing DMH, and they found that administration of vanadium salt not only increased glutathione S-transferase and cytochrome P450 activity in the liver but also slowed tumor growth [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is one of the most popular natural polyphenols derived from Curcuma longa L. It demonstrates a wide spectrum of properties, especially useful in the pharmaceutical and the food industries (Li et al 2016;Liu et al 2015). However, its bioavailability is low due to low solubility, poor stability, and other factors; thus, the application of curcumin in food and medicine is limited (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes without isolated free drugs were dissolved in 10% Triton X-100 and PBS. The EE was determined by dividing the amount of drug in the liposome fraction by the amount of drug in total fractions [ 20 ].…”
Section: Methodsmentioning
confidence: 99%